Genome Organization of a New Double-Stranded RNA LA Helper Virus From Wine Torulaspora delbrueckii Killer Yeast as Compared With Its Saccharomyces Counterparts - Ramírez, Manuel; Velázquez, Rocío; Maqueda, Matilde; Martínez, Alberto (Frontiers in Microbiology, 2020)
Wine killer yeasts such as killer strains of Torulaspora delbrueckii and Saccharomyces cerevisiae contain helper large-size (4.6 kb) dsRNA viruses (V-LA) required for the stable maintenance and replication of killer medium-size dsRNA viruses (V-M) which bear the genes that encode for the killer toxin. The genome of the new V-LA dsRNA from the T. delbrueckii Kbarr1 killer yeast (TdV-LAbarr1) was characterized by high-throughput sequencing (HTS). The canonical genome of TdV-LAbarr1 shares a high sequence identity and similar genome organization with its Saccharomyces counterparts. It contains all the known conserved motifs predicted to be necessary for virus translation, packaging, and replication. Similarly, the Gag-Pol amino-acid sequence of this virus contains all the features required for cap-snatching and RNA polymerase activity, as well as the expected regional variables previously found in other LA viruses. Sequence comparison showed that two main clusters (99.2–100% and 96.3–98.8% identity) include most LA viruses from Saccharomyces, with TdV-LAbarr1 being the most distant from all these viruses (61.5–62.5% identity). Viral co-evolution and cross transmission between different yeast species are discussed based on this sequence comparison. Additional 5′ and 3′ sequences were found in the TdV-LAbarr1 genome as well as in some newly sequenced V-LA genomes from S. cerevisiae. A stretch involving the 5′ extra sequence of TdV-LAbarr1 is identical to a homologous stretch close to the 5′ end of the canonical sequence of the same virus (self-identity). Our modeling suggests that these stretches can form single-strand stem loops, whose unpaired nucleotides could anneal to create an intramolecular kissing complex. Similar stem loops are also found in the 3′ extra sequence of the same virus as well as in the extra sequences of some LA viruses from S. cerevisiae. A possible origin of these extra sequences as well as their function in obviating ssRNA degradation and allowing RNA transcription and replication are discussed.